2013
DOI: 10.1088/0029-5515/53/12/123012
|View full text |Cite
|
Sign up to set email alerts
|

MHD and gyro-kinetic stability of JET pedestals

Abstract: The pedestal profile measurements in high triangularity JET plasmas show that with low fuelling the pedestal width decreases during the ELM cycle and with high fuelling it stays constant. In the low fuelling case the pedestal pressure gradient keeps increasing until the ELM crash and in the high fuelling case it initially increases then saturates during the ELM cycle.Stability analysis reveals that both JET plasmas become unstable to finite-n ideal MHD peeling-ballooning modes at the end of the ELM cycle. Duri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
67
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 39 publications
(84 reference statements)
18
67
0
Order By: Relevance
“…Consequently it may not be appropriate to perform an EPED comparison for all pulses within the new fuelling database. We note that if resistive effects or an effect associated with Type II ELMs were able to hold the pressure gradient slightly below the KB critical value, this would result in a prediction of a somewhat wider and higher pedestal [52,53], which would be qualitatively consistent with observations. …”
Section: Eped Comparisonsupporting
confidence: 74%
See 3 more Smart Citations
“…Consequently it may not be appropriate to perform an EPED comparison for all pulses within the new fuelling database. We note that if resistive effects or an effect associated with Type II ELMs were able to hold the pressure gradient slightly below the KB critical value, this would result in a prediction of a somewhat wider and higher pedestal [52,53], which would be qualitatively consistent with observations. …”
Section: Eped Comparisonsupporting
confidence: 74%
“…On average there is good agreement between the model results and the experimental pre-ELM measurements where the average ratio of predicted pedestal height to observed pedestal height is 1.04±0.22 and the average ratio of predicted pedestal width to observed pedestal width is 1.01±0.23. This spread is within the range of EPED predictive accuracy as observed in a wider multi machine comparison [20,52,53,60]. However the JET results do show a number of differences in comparison to studies on other machines.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In the local linear gyrokinetic analysis of experimental MAST and JET plasmas we have found that, like the n=∞ ideal MHD ballooning modes, the KBMs can access locally so called second stability if the magnetic shear becomes low enough [2,3]. However, in the pedestal region the local assumption that the equilibrium can be considered radially constant for the investigated modes is no longer justified.…”
Section: Introductionmentioning
confidence: 99%